EU adoption of the IFRS 8 standard on operating segments: Note for the ECON Committee of the European Parliament 21 September 2007 - Nicolas Véron (Bruegel, 2007)
In this paper, presented to the Economic and Monetary Affairs Committee of the European Parliament, Nicolas Véron discusses whether the EU should adopt the controversial IFRS 8 standard, a convergence project on how companies should report the performance of their individual business segments. Véron's recommendation is for the European Union not to adopt the current version of IFRS 8.
Keywords: 330; International Financial Reporting Standards; Segmentberichterstattung; EU-Recht; EU-Staaten